Longitudinal Change in Peripheral Anterior Chamber Depth of Eyes with Angle Closure after Laser Iridotomy - Toshie Furuya; Kenji Kashiwagi (Journal of Ophthalmology)
Purpose. To investigate longitudinal changes in peripheral anterior chamber depth (pACD) of eyes with angle closure after laser iridotomy (LI) and factors related to prognosis. Design. Retrospective cohort study. Methods. Eyes with primary angle closure (PAC), acute PAC, or chronic angle closure glaucoma (CACG) that underwent LI (LI group) and eyes that underwent phacoemulsification and intraocular lens insertion (PEA + IOL group) were employed. Longitudinal changes in pACD were evaluated with a scanning peripheral anterior chamber depth analyzer (SPAC) in addition to routine ophthalmic examination. Results. Forty-eight eyes of LI groups (69.8 ± 8.5 years) and 21 eyes of PEA + IOL group (65.6 ± 12.7 years) were enrolled. Mean follow-up times of LI group and PEA + IOL group were 43.4 ± 12.7 months and 36.5 ± 2.5 months, respectively. LI significantly increased pACD as indicated by the SPAC grade change from 3.8 ± 1.1 to 4.6 ± 1.2 (p<0.001). However, SPAC grade was gradually reduced and reached the pre-LI level by the third year of follow up. PEA + IOL also significantly increased SPAC grade from 6.7 ± 1.6 to 8.7 ± 2.0 (p<0.001), but no time-related change was observed. Twenty-three cases of LI group presented with deterioration of glaucoma control. The type of angle closure, plateau iris configuration, peripheral anterior synechia, and glaucomatous visual field defects were significantly associated with prognosis of glaucoma after LI. Conclusions. Peripheral ACD is temporarily deepened by LI, but returns to the pre-LI level in approximately three years. The type of angle closure and some factors may be related to glaucoma prognosis after LI.